Studi Penentuan Daya Tampung Beban Pencemaran Sungai Bedadung Kabupaten Jember Menggunakan Program QUAL2Kw - Elida Novita; Rodzika Diah Mauvi; Pradana, Hendra Andiananta (Jurnal Keteknikan Pertanian, 2022)
Bedadung River is the main river that passes through Jember Regency. The river is a source of raw water for Perumdam which provides a clean water supply for the city community. The increase in population in the area has an impact on high community activities which result in a decrease in the water quality of the Bedadung River, so there is a need for water quality management efforts. This study aims to assess the water quality of the Bedadung River using QUAL2Kw modeling in order to obtain river water quality according to its use. The methods used include segmentation, calibration, verification, simulation, calculation of pollution load and pollution load capacity. The results showed that Bedadung River (Patrang – Ajung segment) have the maximum pollution load capacity on the COD and TSS parameters of 16.50 kg/day and 6061.56 kg/day, respectively. Then, the BOD parameter is -2.43 kg/day. A negative value on the total pollution load capacity indicates that the river can no longer accommodate incoming pollutants exposure.